Green human resource management and the enablers of green organisational culture: Enhancing a firm's environmental performance for sustainable development - Roscoe, Samuel; Subramanian, Nachiappan; Jabbour, Charbel J.C.; Chong, Tao (Business strategy and the environment, 2019)
Scholars have shown that green human resource management (GHRM) practices enhance a firm's environmental performance. However, existing studies fail to explain how GHRM initiatives can enable a green organisational culture or how such a culture affects the environmental performance and sustainable development of the firm. This paper examines the relationship between GHRM practices, the enablers of green organisational culture, and a firm's environmental performance. We conduct a large‐scale survey of 204 employees at Chinese manufacturing firms. Our findings suggest that proenvironmental HRM practices including hiring, training, appraisal, and incentivisation support the development of the enablers of green organisational culture. We suggest the key enablers of green organisational culture include leadership emphasis, message credibility, peer involvement, and employee empowerment. Our paper contributes to HRM theory in terms of originality and utility of research by explaining that the enablers of green organisational culture positively mediate the relationship between GHRM practices and environmental performance. Managers are provided with a detailed understanding of the GHRM practices needed to enable an organisational culture of environmentally aware employees. Finally, we address potential implications of this work for teaching green organisational culture to future generations of responsible managers.